Making the selective agent for the Bar plasmids, phoshoinothricin (glufosinate) affordable for routine use - R L Metzenberg; D J Jacobson; H Bertrand (Fungal Genetics Reports, 2000)
Phosphinothricin (glufosinate) is an antimetabolite that has been used for the selection of fungal transformants carrying the Bar plasmid and its various derivatives. The cost of the pure material has limited its usefulness as a selective agent. We describe a purification of glufosinate from an inexpensive commercial source.